BLENDED LANGUAGE LEARNING: INTEGRATING DIGITAL, TRADITIONAL, AND CREATIVE APPROACHES FOR EFFECTIVE LANGUAGE ACQUISITION - Maftuna Sultonova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper examines the effectiveness of a blended approach to foreign language learning that integrates traditional teaching methods, digital tools, immersive experiences, and creative strategies. Unlike single-method instruction, this study highlights how combining multiple approaches can enhance learner engagement and improve language proficiency. Drawing on previous research and comparative analysis, the study evaluates how each method contributes to vocabulary development, grammar acquisition, pronunciation, and communicative competence. Findings indicate that while traditional methods provide a strong structural foundation, digital tools offer flexibility and accessibility, immersive environments enhance real-life communication, and creative techniques such as music increase motivation and retention. The study concludes that a hybrid model of language instruction leads to more comprehensive and meaningful learning outcomes.